Social Representations of Health Awareness During covid19 in Cities: Micro sociological Approach - Mabrouki, Amar (Journal of Human Sciences, 2023)
The study aims to reveal the social representations of health awareness during the Corona virus (Covid 19) pandemic in the urban environment from the point of view of microsociology, in particular the spread of infection, it is a theoretical study , through which we have tried to reveal the implicit aspect of health awareness by pressing the sociological side, and, the descriptive approach and the qualitative analysis of the behaviors and interactions of individuals faced with the health crisis have been used, direct observation on the prevention of infectious diseases the study led to several results, the most important of which are: - the prevention of diseases could not reach its objectives - Fear of the pandemic pushed individuals to self-medicate and to acquire drugs without consulting specialists - the silence towards the disease and not to declare, has aggravated the situation.